Ragam Solusi Ekonomi Islam dalam Mengatasi Masalah Ekonomi - Kurniawan, Rachmad Risqy; Putri, Talitha Destiani; Sufni, Adria Zahrani (Ulumul Qur’an: Jurnal Kajian Ilmu Al-Qur’an dan Tafsir, 2022)
The purpose of this study is to examine more deeply about the various solutions of Islamic economics in overcoming economic problems, especially the economic crisis based on the verses of the Qur'an and their interpretations. This research is library research with the maudhu'i (thematic) interpretation method. The results of this study indicate that so far the solution to Indonesia's economic problems has always relied on only one policy, namely debt, while Islamic economics provides various solutions in dealing with economic problems, one of which is the economic crisis. As in the interpretation of QS. Yusuf verse 67 then in solving economic problems, Islamic economics does not use only one door or only one solution or one approach/method, but comes from various doors, namely using several approaches/methods that are solutions to economic problems, especially crises, so that the results achieved as expected and avoid failure in an effort to solve economic problems.